Impaired Intestinal Mucosal Barrier upon Ischemia-Reperfusion: "Patching Holes in the Shield with a Simple Surgical Method". (14th May 2014) - Rosero, Olivér; Ónody, Péter; Kovács, Tibor; Molnár, Dávid; Lotz, Gábor; Tóth, Szilárd; Turóczi, Zsolt; Fülöp, András; Garbaisz, Dávid; Harsányi, László; Szijártó, Attila
Abstract : Mesenteric ischemia-reperfusion (IR) is associated with impairment of the gut barrier function and the initiation of a proinflammatory cascade with life-threatening results. Therefore methods directed to ameliorate IR injury are of great importance. We aimed at describing the effects of postconditioning (PC) on the alterations of the intestinal mucosal function and the inflammatory response upon mesenteric IR. Methods . Male Wistar rats were gavaged with green fluorescent protein-expressing E. coli suspensions. Animals were randomized into three groups (n = 15 ), sham-operated, IR-, and PC-groups, and underwent 60 minutes of superior mesenteric artery occlusion, followed by 6 hours of reperfusion. Postconditioning was performed at the onset of reperfusion. Blood and tissue samples were taken at the end of reperfusion, for histological, bacteriological, and plasma examinations. Results . The PC-group presented a more favorable claudin-2, claudin-3, claudin-4, and zonula occludens-1 membrane expression profile, and significantly lower rates of bacterial translocation to distant organs and plasma D-lactate levels compared to the IR-group. Histopathological lesions, plasma I-FABP, IL-6, and TNF- α levels were significantly lower in the PC-group compared to the IR-group. Conclusion . The use of postconditioning improved the integrity of the intestinal mucosal barrier upon mesenteric IR, and thus reduced the incidence of bacterial translocation and development of a systemic inflammatory response.